Batch Tests for Optimisation of Solvent Composition and Process Flexibility of the CHALMEX FS-13 Process. Issue 1 (2nd January 2021) - Lyseid Authen, Thea; Wilden, Andreas; Halleröd, Jenny; Schneider, Dimitri; Kreft, Fabian; Modolo, Giuseppe; Ekberg, Christian
ABSTRACT: Studies have been performed with the purpose of determining the optimal solvent composition of a Chalmers grouped actinide extraction (CHALMEX) solvent for the selective co-extraction of transuranic elements in a novel Grouped ActiNide EXtraction (GANEX) process. The solvent is composed of 6, 6'-bis(5, 5, 8, 8-tetramethyl-5, 6, 7, 8-tetrahydro-benzo-[1, 2, 4]-triazin-3-yl)-[2, 2']-bipyridine (CyMe4 -BTBP) and tri- n -butyl phosphate (TBP) in phenyl trifluoromethyl sulfone (FS-13). The performance of the system has been shown to significantly depend on the ratios of the two extracting agents and the diluent to one another. Furthermore, the performance of the determined optimal solvent (10 mM CyMe4 -BTBP in 30% v/v TBP and 70% v/v FS-13) on various simulated PUREX raffinate solutions was tested. It was found that the solvent extracts all transuranic elements with high efficiency and good selectivity with regard to most other elements (fission products/activation products) present in the simulated PUREX raffinate solutions. Moreover, the solvent was found to extract a significant amount of acid. Palladium, silver, and cadmium were co-extracted along with the TRU-radionuclides, which has also been observed in other similar CHALMEX systems. The extraction of plutonium and uranium was preserved for all tested simulated PUREX raffinate solutions compared to experiments using trace amounts.